Public finance resilience in the transition towards carbon neutrality Modelling policy instruments in a global net-zero emissions - Fouré, Jean (OECD Publishing, 2023)
This paper presents a detailed economic modelling analysis of public finance in the transition towards carbon neutrality. It outlines results from a Net-Zero Emission Ambition scenario, which reflects the ambition to achieve net-zero carbon dioxide emissions globally by mid-century, using a broad and region-specific policy package that combines various policy instruments: carbon pricing, removal of fossil fuel support, regulations in the power sector, and other policies that stimulate investments by firms and households to reduce and decarbonise energy use. The analysis relies on the OECD global computable general equilibrium ENV-Linkages model. Results show that transitioning towards carbon neutrality is feasible when considering economic and fiscal consequences. The scenario achieves carbon neutrality while maintaining continued economic growth, despite a limited negative impact on global GDP and on public revenues. The fiscal effects reflect a trade-off between instruments that increase public revenues (carbon pricing) or reduce public expenditures (fossil fuel subsidies removal), on the one hand, and more costly instruments (subsidies) and indirect effects (tax base erosion and changes in fiscal and economic structure) on the other hand
Keywords: Environment